Psychological/Moral Workplace Harassment: Development of an Inventory in Argentina - Eduardo Mario Bustos Villar; Marcelo Carlos Caputo; Silvia Elizabeth Aranda Coria; Nadia Messoulam (Social Medicine Publication Group, 2024)
It is estimated that workplace harassment has a high incidence rate within the workforce. It generates negative health consequences and an array of psychosocial problems. The knowledge gaps on the issue make it difficult to evaluate, and create a situation of impotence for the affected workers, perpetuating a silence on the part of those subjected to these attacks. Without being identified as victims of workplace harassment, they are dealt with using non-specific approaches. The scientific evaluation of harassment is an area lacking today in Argentina. The objective is to present a process for the construction of a technique to evaluate psychological workplace harassment within our current socio-cultural context. The stages of this process are: literature review, interviews with key informants and worker-victims, creation and adaptation of an item list, review by expert judges, filtering of item list and use in pilot sample, and an analysis of the validity of items. A reliable instrument was constructed for the evaluation of the phenomenon in our context: the Inventory of Workplace Harassment (Inventario de Hostigamiento Laboral) (IWH, Bustos Villar, Caputo and Aranda Coria, 2011) composed of four scales that identify situations of harassment, those being communication, work, private life, and facilitating environment. In a second component it reveals information about characteristics of the perpetrator and the perceived consequences. KEY WORDS: workplace harassment, inventory, Argentina